Pendekatan Gerakan Lingkungan Hidup yang Diterapkan pada Program REDD+ di Kabupaten Berau - Ardani, Rafi; Hamid, Ismar (Prodi Sosiologi FISIP ULM, 2025)
The REDD+ programme aims to curb deforestation, with Berau Regency as one of the target areas with a commitment to implement the programme until 2030. The purpose of this research is to examine the environmental movement approach applied to the REDD+ programme and its impact on the sustainability of local livelihoods in Berau Regency. This research focuses on the REDD+ programme implemented by non-government organisations (NGOs), namely YKAN, PERISAI, Forclime, and SRP Payo-Payo. This research uses a qualitative method with a case study research approach. Data collection techniques used candid observation, semi-structured interviews and documentation. Data was analysed using an interactive model. The results show that the approach applied to the implementation of REDD+ programmes by non-government organisations (NGOs) in Berau Regency is a participatory approach, where the community acts as the main actor in every programme implementation. This approach is supported by the paradigm of the eco-populism environmental movement, which pays attention to aspects of local knowledge and the sources of life of local communities. The presence of the REDD+ programme does not disrupt livelihoods and does not change the culture of local communities, or integrate the objectives of the REDD+ programme with aspects that already exist in the community. The implication is that with the REDD+ programme, the community gets additional sources of livelihood without reducing the existing sources of livelihood that have been carried out for generations. Furthermore, the REDD+ programme is able to stimulate the community to abandon unsustainable practices. The REDD+ programme in Berau Regency should continue to be implemented by making local communities the main actors and adhering to local wisdom that exists in the community.